Violence workers : police torturers and murderers reconstruct Brazilian atrocities - Huggins, Martha Knisely, 1944-; Haritos-Fatouros, Mika, 1930-2014; Zimbardo, Philip G. (Berkeley : University of California Press, 2002)
Of the 23 Brazilian policemen interviewed in depth for this landmark study, 14 were direct perpetrators of torture and murder during the three decades that included the 1964-1985 military regime. The policemen help answer questions that haunt today's world.
List of Tables, Figures, and Photographs; Acknowledgments; Preface; Introduction; 1. Violent Lives; 2. Reconstructing Atrocity; 3. Locating Torturers and Murderers; 4. Deposing Atrocity and Managing Secrecy; 5. Biography Intersects History; 6. Personalistic Masculinity; 7. Bureaucratizing Masculinity; 8. Blended Masculinity; 9. Shaping Identities and Obedience: A Murderous Dynamic; 10. Secret and Insular Worlds of Serial Torturers and Executioners; 11. Moral Universes of Torturers and Murderers; 12. Hung Out to Dry; Conclusion: The Alchemy of Torture and Execution; References; Index.
Includes bibliographical references (pages 269-281) and index.
Print version record.
English.
JSTOR
Keywords: Police brutality -- Brazil; Political atrocities -- Brazil; Torture -- Brazil; Brutalités policières -- Brésil.; Atrocités politiques -- Brésil.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; SOCIAL SCIENCE -- Anthropology -- Cultural; Police brutality; Political atrocities; Torture; Brazil; Geweld; Martelen; Politie; Psychologische aspecten; Brazilië; Casestudies (vorm)